Rejuvenation of Coastal Area in Selumit Pantai Village Tarakan City - Andri Putra Naftali; Ardhya Nareswari (Department of Architecture Universitas Muhammadiyah Jakarta, 2024)
Tarakan City, as the only city in North Kalimantan, has a Coastal settlement in Selumit Pantai Urban Village. According to the RP2KPKP Study, this area is experiencing slum problems due to environmental degradation and lack of basic infrastructure. To address this, a study was conducted to identify slum levels and formulate appropriate rejuvenation strategies. By conducting rejuvenation, the condition of slum-affected neighborhoods can be improved, providing a positive impact on residents and the surrounding environment. This research used quantitative methods with seven slum indicators and consideration of population and socio-economic conditions. The results showed all blocks as severe slums, so priority Urban Renewal strategies were applied to reduce slum levels. The research findings confirmed that the coastal area faced severe slum levels, due to building density, environmental degradation, and lack of adequate infrastructure. The Regeneration Strategy implemented aims to improve and renew degraded areas, taking into account aspects of economic growth and environmental conservation. These efforts, such as improving infrastructure and environmental quality, are expected to reduce slum levels in the area, improve community welfare, and maintain the sustainability of the coastal environment, creating a better environment for its residents. Keywords: Tarakan City, coastal, Slum, Area rejuvenation, Regeneration strategy